Law Enforcement against Medical Waste Management Negligence Covid-19 Sample Examination by Start-Up Companies - Wijaya, Hanna; Haryanto, Imam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The world is being shocked by the COVID-19 disease, which has quickly evolved into a pandemic. rRT-PCR is used to examine this disease. This attracts a large number of Start-Up companies to the health industry, resulting in a significant increase in medical waste. As an outcome, medical waste that is not appropriately managed in accordance with SOP accumulates. There are quite a few people who carelessly discard medical waste. This journal is a juridical-normative study. If not correctly managed, the outcomes of this investigation in the form of medical waste can pollute the environment and endanger surrounding populations. The study's conclusion is that medical waste must be carefully managed in compliance with SOP. Individuals who fail to properly handle medical waste will face criminal consequences under the criminal code of law.